Female Consumers Perception On Luxury Products - G, Indhumathi; v, vasanthakumar; A, Ramamani (Social Science Studies, 2024)
The attitude of women on buying luxury products from various brand got increased nowadays. Women often view luxury products as a way to express their personal style, feel confident and empowered, and signal their social status to others. The paper aims at understanding the factors influencing the attitude of female consumers towards the luxury products and behaviour and finds that product quality has a major factor for buying luxury products. The research was made with primary data through Questionnaire and collected 120 samples from random population. The paper results that luxury products have a higher influence on female consumers and Luxury brands use various marketing strategies to target female consumers, such as emphasizing the product's quality, exclusivity, and emotional appeal. the researcher concludes with the data that decision to choose the luxury products is personal for women consumers rather than social values.